Carrot pectin enriched fraction as a functional additive: Antioxidant and gelling effects in a model spreadable chia oil-in-water emulsion. (November 2020) - Idrovo Encalada, Alondra M.; Pérez, Carolina D.; Rossetti, Luciana; Rojas, Ana M.; Fissore, Eliana N.
Abstract: An orange-colored pectin-enriched fraction previously obtained from discarded carrots (CPEF; 42%-methylated, 14%-acetylated, 50% uronic acids) through high-power-ultrasound and bacterial hemicellulase, carrying carotenes, lutein, and α-tocopherol, was evaluated as a food additive for its capacity to stabilize a model spreadable 20:80 w/w chia-oil-in-water emulsion. The optimal formulation for physical stability after 45 days at 25 °C was first determined through a Box-Behnken design with three independent variables (CPEF and Tween 80 concentrations, and ultrasound-emulsifying time). The optimized CPEF emulsion constituted a calcium-crosslinked "weak-gel type" network formed by the contribution of oil droplets. During storage, its elastic modulus increased probably by CPEF adsorption at the interface. In the optimized emulsion, CPEF prevented oil-phase oxidation by the air-oxygen entrapped, through the 45 day storage (peroxide index: 7.6meq/kg oil-phase; TBARS: 6.0 mg MDA eq/kg oil-phase), based on the differential partition of antioxidants between the interior of the oil droplets (apolar carotenes) and the oil-water interface (more polar tocopherol), the latter formed by the nonionic Tween 80 emulsifier. Despite unfavorable conditions for the preservation of food systems (water activity = 0.979; pH 5.4; air-oxygen; 25 °C), the emulsion orange-color was highly stable during storage due to the stability of carotenoids. CPEF is thus a useful functional additive for food preservation. Graphical abstract: Image 1 Highlights: A carotenoids-tocopherol rich orange-color pectin from carrot (CPEF) was evaluated. CPEF formed a weak gel network that stabilized the emulsion system. CPEF raised 20:80 chia-oil/water emulsion elasticity during 45-days-storage (25 °C). CPEF gel network entrapped oil drops and delayed greatly the chia-oil-phase oxidation. CPEF stabilized the orange-color of the emulsion and, hence, carotenoids-tocopherol.